A contribution to understanding metallurgic activities of the Liburnians (Archaeologia Adriatica, 2013)
Despite abundance of autochthonous metal forms we know very little about the process of production of metal objects in the Liburnians. Metallurgic centres, workshops and tools are unknown for the most part. Only scarce examples of moulds stand as indicators of production. Their existence opens up discussion about the technology of production, skills and achievements of the Liburnian producers.
Keywords: metallurgy; moulds; Liburnians